Feasibility study of a reconfigurable fiber-wireless testbed using universal software radio peripheral - Ridwan M.A.; Radzi N.A.M.; Abdullah F.; Din N.M.; Rashidi C.B.M. (Taiwan Association of Engineering and Technology Innovation, 2023)
Fiber-wireless (FiWi) network is still improved ongoingly and there are a number of testbeds for the FiWi network available nowadays. However, most of them are hardware-based, making them not easy to reconfigure to perform architecture or protocol studies. This paper first proposes a reconfigurable FiWi testbed using software-defined radio, particularly universal software radio peripheral (USRP) with LabVIEW as the simulation platform. To evaluate the testbed, wireless range and power output were tested to optimize the best output for the USRP. With the range of 100 m, it was found that the best output power is 30 dB. Then, the study evaluated the performance of the upstream FiWi testbed transmission in terms of throughput, transmission time, and jitter. To test the testbed reconfigurability, the testbed architecture and transmission type were altered, and the performance was scrutinised. The experimental results indicate that USRP is suitable for a reconfigurable FiWi testbed. TAETI.